Pengaruh Capital Adequancy Ratio, Net Interest Margin,Biaya Operasional Pendapatan Operasional Dan Loan Deposit Ratio Terhadap Non Performing Loan Di Pt. Bank Pembangunan Daerah Bali Tahun 2009 – 2017 - Ni Wayan Eka Yuliani; A. A. Sri Purnami; I Gusti Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2020)
NPL is one indicator in assessing the soundness of banks. This study aims to examine the effect of CAR, NIM, BOPO and LDR on Non Performing Loans at PT. Regional Development Bank of Bali in the count of I - IV in 2009 - 2017 using multiple linear analysis methods. The results of this study produce an F Test which all independent variables (CAR, NIM, BOPO and LDR) have a liner / influence with NPL variables and partially, CAR has a significant and significant effect on NPL, NIM has a positive and not significant effect on NPL, influential BOPO positive and significant effect on NPL and LDR positive and not significant effect on NPL.